Comparative study of irrigation efficiency during HoLEP and morcellation - Ohno, Yoshio; Hashimoto, Takeshi; Hayashi, Kenjiro; Ishida, Takuya; Shishido, Toshihide; Namiki, Kazunori; Aizawa, Taku; Satake, Naoya (Japanese Journal of Endourology, 2021)
We investigated the safety of and effective irrigation methods for holmium laser enucleation of the prostate (HoLEP) and tissue morcellation with and without using a lure lock cock with three companies’ endoscopes. Furthermore, the flow rates of the three companies’ irrigation tubes were compared. The flow rate exceeded 500 mL per minute for all manufacturers on performing HoLEP. In the morcellation setting, the presence of a lure lock cock did not affect the flow rate. The inflow rate of the irrigation port of the nephroscope in single route was lower than that of the outer sheath. The irrigation tube with the highest flow rate was had a large inside diameter and four connecting tubes.  It is important to consider the difference in flow rates due to the difference in connection routes of an endoscope and choose an efficient irrigation route using a lure lock cock.